2017
DOI: 10.1371/journal.pone.0189381
|View full text |Cite
|
Sign up to set email alerts
|

Proteometabolomic response of Deinococcus radiodurans exposed to UVC and vacuum conditions: Initial studies prior to the Tanpopo space mission

Abstract: The multiple extremes resistant bacterium Deinococcus radiodurans is able to withstand harsh conditions of simulated outer space environment. The Tanpopo orbital mission performs a long-term space exposure of D. radiodurans aiming to investigate the possibility of interplanetary transfer of life. The revealing of molecular machinery responsible for survivability of D. radiodurans in the outer space environment can improve our understanding of underlying stress response mechanisms. In this paper, we have evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 80 publications
1
45
0
Order By: Relevance
“…The protein band observed at~40 kDa was excised (Uni-Prot Acession: A0A0E3K5T7-slaB = 41 kDa), processed for mass spectrometric analysis and subsequent protein identification as described in ref. 72 .…”
Section: Methodsmentioning
confidence: 99%
“…The protein band observed at~40 kDa was excised (Uni-Prot Acession: A0A0E3K5T7-slaB = 41 kDa), processed for mass spectrometric analysis and subsequent protein identification as described in ref. 72 .…”
Section: Methodsmentioning
confidence: 99%
“…Although limited under space-simulated conditions, previous studies have shown a similar tendency after exposure of D . radiodurans to UVC radiation combined with vacuum and solely vacuum [ 23 , 24 ]. Our untargeted metabolomics approach indicated a reduced level of sugars during repair after LEO exposure (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary experiments with monochromatic lamps at UV 172 nm UV 254 nm, indicated that cells of D. radiodurans should be able to withstand solar UV radiation on the ISS for 1 year as multi-layers of more than 200 μm thickness [ 21 ]. Additionally, several initial investigations prior to the Tanpopo space mission already resolved molecular responses of D. radiodurans to selected simulated parameters of the outer space environment [ 23 , 24 ]. Exposure to extreme conditions such as ionizing radiation, UV radiation and desiccation cause an increase of reactive oxygen species, which severely damage nucleic acids, by forming bipyrimidine dimers or introducing DNA double strand breaks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of hydrolases 390 modulating cellular redox processes has been described for many organisms [56] and in 391 D. radiodurans it prevents incorporation of damaged nucleotides into DNA [1] [38]. RNA enzymes are essential for stress resistance [43] [1] [39] [38].…”
mentioning
confidence: 99%